With friends like these : a novel - Lee, Alissa (Emily Bestler Books/Atria, 2025)
Former Harvard roommates maintain a long-standing secret tradition called the Circus, a campus-inspired elimination game, twenty years after graduation. When a hidden prize is revealed, what began as a harmless game escalates into a dangerous contest as past secrets resurface. The story explores friendship, loyalty, and the consequences of long-held secrets against a suspenseful, urban backdrop.